Pos UKK Cumi dan Pos UKK Kerapuh Sebagai Upaya Meningkatkan Kesehatan Keluarga di Wilayah Tambakwedi Kecamatan Kenjeran, Surabaya - Wiliyanarti, Pipit Festi; Aryunani, Aryunani; Sumarliyah, Eni (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
UKK Kerapuh and UKK Cumi  not develop because of the low participation of fishing communities in the region in the implementation of the program Tambak Wedi  UKK . Volunteers or health workers who are not active, people do not understand about the benefits and management of UKK .Health education activities have not been carried out routinely by cadres of health workers. Poor work habits, among others squat and bend over too long, working without protective , complaints Hypertension disease, respiratory illness, back pain, skin diseases on the fishermen.The  Matter UKK group health was hypertension, disorders of the respiratory tract (cough), family members of fishermen 10% are anemic.The approach offered to resolve the issue is to carry out workshops, training and mentoring, in improving the skills of cadre pos UKK and the fishing communities of Tambakwedi region, help improve management capabilities UKK .Output Increased knowledge and skills of partners in managing the UKK, healthy eating family management skills, Training Module Health and Safety, Management Pos UKK, Scientific; Proceending; and Poster.